ESCAPE: Interactive fire simulation and training for children using virtual reality - Ahmad, W.F.W. (2019)
Fire accident is a destructive disaster that has caused many property damages, injuries and even fatal. Lack of fire safety knowledge is one of the factors that lead to the horrendous experience of fire especially among young children and senior citizens. Conventional training usually does not assess the ability of the children to do practical skills on escaping out of fire but rather of fire drill on remembering escape route to fire point. Therefore, this project focuses on developing fire training and simulation for children by using virtual reality. The objective of the paper is to present a fire drill in the form of simulation and interactive training by using Virtual Reality. The simulation has been developed using Unity 3D and HTC Vive. Rapid application development was chosen for this development. A usability testing has been conducted with 10 participants. An interview has also been conducted with one of the school teachers. The results show that this project is beneficial and gives addition to the approaches of fire safety practice and allow children to learn better by improving their knowledge on fire safety. Â© Springer Nature Switzerland AG 2019.